2012
DOI: 10.1371/journal.pone.0052344
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and Biological Gene-Lifestyle Interactions of MC4R and FTO with Diet and Physical Activity on Obesity: New Effects on Alcohol Consumption

Abstract: BackgroundFat mass and obesity (FTO) and melanocortin-4 receptor (MC4R) and are relevant genes associated with obesity. This could be through food intake, but results are contradictory. Modulation by diet or other lifestyle factors is also not well understood.ObjectiveTo investigate whether MC4R and FTO associations with body-weight are modulated by diet and physical activity (PA), and to study their association with alcohol and food intake.MethodsAdherence to Mediterranean diet (AdMedDiet) and physical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 62 publications
7
53
1
4
Order By: Relevance
“…Using a multiple linear regression model with the inclusion of a cross-product term signifying the product of environmental (E) and genetic (G) variables is the most common method to assess interactions [107,114,117,125]. Coding genetic polymorphisms is either performed to create a binary variable (under a recessive or dominant model) or a three-category variable based on an additive model, with the latter often used when the true functional model of a given marker is not known [261].…”
Section: Statistical Modelling Issues In Gene-environment Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a multiple linear regression model with the inclusion of a cross-product term signifying the product of environmental (E) and genetic (G) variables is the most common method to assess interactions [107,114,117,125]. Coding genetic polymorphisms is either performed to create a binary variable (under a recessive or dominant model) or a three-category variable based on an additive model, with the latter often used when the true functional model of a given marker is not known [261].…”
Section: Statistical Modelling Issues In Gene-environment Interactionmentioning
confidence: 99%
“…The value of improving measurement accuracy as opposed to increasing sample size can be reinforced with the example of physical activity measurement, a common exposure analysed in gene-environment interactions of obesity [117,125,269]. Physical activity is usually assessed by questionnaire, and even comprehensive instruments that address occupational and leisure activity rarely correlate with objective measures of energy expenditure above 0.3 [321].…”
Section: Measurement Issues In Gene-environment Interactions Researchmentioning
confidence: 99%
“…Continuing with the classic polymorphisms, we analyzed the influence of the MeDiet and fat intake on the effects of CETP polymorphisms (24502C > T and the TaqIB) on lipids (44). In another study, we focused on gene-diet interactions determining obesity (45). A genetic score, including the melanocortin 4 receptor (MC4R) rs17782313 and fat mass and obesity (FTO) rs9939609 variants, was strongly associated with BMI; although there was no statistically significant interaction with the MeDiet, greater adherence significantly reduced BMI in genetically susceptible individuals.…”
Section: Current Status Of Knowledge: the Predimed Studymentioning
confidence: 99%
“…In line with these results, A-allele carriers were reported to consume more meals per day and eat more energy dense foods [62]. However, in study of Corella et al [63], no association between FTO and general food intake or food groups was found, but alcohol consumption in variant allele carriers was significantly lower than in wild-type subjects. Interestingly, AA genotype subjects presented also the highest rate of under-reporting of energy intake (17%) compared to TT genotype (15.4%), which was also more frequent in obese population [61].…”
Section: Fto and Dietmentioning
confidence: 62%
“…For example, Razquin et al [66] have demonstrated that a Mediterranean-based diet, rich in mono-and polyunsaturated fat, provides FTO risk allele carriers some protection against body weight gain after three years of nutritional intervention. Also Corella et al showed that high adherence to a Mediterranean diet can counterbalance the genetic susceptibility to obesity [63]. In the Malmo Diet and Cancer Study, fat intake was shown to accentuate the effect of FTO on obesity.…”
Section: Prace Poglądowementioning
confidence: 99%